1993
DOI: 10.1002/nbm.1940060109
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 31P MRS of the normal adult human brain. Assessment of interindividual differences and ageing effects

Abstract: The characteristics of the 31P MR spectra from a large central volume in the brain of 47 healthy adults (aged 25-85 years) were assessed. Spectral parameters were estimated by means of a time-domain fitting technique. Statistical uncertainties of the estimates were determined by means of the Cramer-Rao theory and minimized by introducing a priori knowledge into the fitting procedure. Age-dependency of the spectral parameters was assessed by means of linear regression. Significant differences between individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 10 publications
5
24
0
Order By: Relevance
“…The observation of no age-related change in Pi/ATP agrees with those previously made by others [25,26]. This does not, however, necessarily mean that there is no age-related change in any of the constituents of these ratios.…”
Section: Brain Bioenergetics and Agesupporting
confidence: 81%
See 2 more Smart Citations
“…The observation of no age-related change in Pi/ATP agrees with those previously made by others [25,26]. This does not, however, necessarily mean that there is no age-related change in any of the constituents of these ratios.…”
Section: Brain Bioenergetics and Agesupporting
confidence: 81%
“…A study of children aged from 1 to 16 years has reported similar results but no agerelated change in pH, and no significant changes in the spectrum after the age of 3 years [25]. A study of adults aged 25-85 years [26] has reported no change in pH across this age range, but a significant (p ! 0.001) increase in the intensity of PCr.…”
Section: Brain Bioenergetics and Agesupporting
confidence: 51%
See 1 more Smart Citation
“…age, including increases in phosphocreatine and ATP [73,82,83] suggesting that total brain bioenergetics capacity increases rather than decreases with age. With increased creatine improving brain function, the reverse has also been shown, where memory exercises have been shown to increase levels of creatine in the hippocampus of healthy elderly performing training in the Method of Loci task, involving delayed recall, spatial and associative memory training, compared to elderly subjects who were merely undertaking tasks of everyday living [84].…”
Section: Roles Of Creatine In the Brainmentioning
confidence: 96%
“…Longo and coworkers [60] showed an age-dependent decrease in the PCr line intensity obtained from a large central volume of brain in healthy volunteers. The study volume included both gray and white matter.…”
mentioning
confidence: 98%